KEPUASAN DAN LOYALITAS KONSUMEN IBU RUMAH TANGGA DALAM MENGONSUMSI SANTAN SUN KARA DI KOTA BANDAR LAMPUNG - Maulina Tunjungsari; Dwi Haryono; Dyah Aring Hepiana Lestari (Lampung University, 2015)
The aim of this research was to determine the pattern of consumption, satisfaction, and customer loyalty of Sun Kara coconut milk in Bandar Lampung. This research was conducted in May 2014 until June 2014 by survey method through interviewing respondents. Total respondents were 80 housewives. The research was conducted at traditional market, stall, minimarket, and supermarket in Sukarame Subdistrict and Rajabasa Subdistrict. The data analysis’ tools were Customer Satisfaction Index (CSI) and the analysis of switcher buyer, habitual buyer, satisfied buyer, liking the brand and committed buyer. The result showed that the frequency of purchasing Sun Kara coconut milk is 3-4 times and the amount of purchasing Sun Kara coconut milk ranged between 62-200 ml per month. Consumers often buy Sun Kara coconut milk in a stall and Sun Kara coconut milk is usually used for cooking ingredients. Most respondents were unaware of the content contained in Sun Kara coconut milk. The calculation’s result of Customer Satisfaction Index (CSI) obtained values ​​of customer satisfaction 73% which means that consumers were satisfied with Sun Kara coconut milk product. Respondents that categorized as switcher buyer were 8.75%. The number of respondents that bought Sun Kara coconut milk as habitual buyer was 41.25%. Respondents that categorized as satisfied buyer were 66.25%. The number of respondents that categorized as liking the brand was 55%. Consumers that categorized as committed buyer were 33.75%. Key words: coconut milk, customer satisfaction index, loyalty, satisfaction, sun kara